Cross-cultural Adaptation and Validation of the Greek Voice Handicap Index-10 (GVHI-10) With Additional Receiver Operating Characteristic Analysis - Tafiadis, Dionysios; Helidoni, Meropi E.; Chronopoulos, Spyridon K.; Kosma, Evangelia I.; Ziavra, Nafsika; Velegrakis, George A. (Journal of voice, 2020)
The use of subjective evaluation tools are proven useful and of high clinical value in the case of voice disordered population. For that type of evaluation, self-assessment questionnaires about the severity of the voice like Voice Handicap Index-30 (VHI-30) have been developed. The VHI-30 is the most studied tool which includes psychometrically robustness while guiding physician's therapeutic decision making. Additionally, a valid abbreviated version of VHI-30 was developed for the first time in the Greek Language which is named as Greek Voice Handicap Index-10 (GVHI-10). Consequently, the aim of our study was to validate the proposed version of the VHI-10. Ninety nondysphonic individuals and 90 dysphonic patients were classified by Otolaryngologists and Speech Language Pathologists. The study's subjects were evaluated with endoscopy and stroboscopy. Also, they were administrated the GVHI-30 and the translated version of the Voice Evaluation Template (VEF). The GVHI-10 was extracted by the Greek version of VHI-30. The group with voice disorders exhibited higher statistical significance in all GVHI-10 scores compared to those of the control group. The GVHI-10 showed a high internal consistency (Cronbach's a = 0.915 and split-half reliability coefficient equal to 0.86), good sensitivity compared to Greek VHI-30 (r = 0.764, P = 0.000) and intraclass correlation. A total cut-off point equal to 6.50 (AUC: 0.964; P < 0.001) was also calculated. The proposed version of GVHI-10 distinguished the perceived levels of voice between dysphonic and nondysphonic groups and between different voice disordered populations. The GVHI-10 is shown to be clinically valid and sensitive exhibiting high reliability.